2023
DOI: 10.3389/fmicb.2023.1113174
|View full text |Cite
|
Sign up to set email alerts
|

Identifying microbial signatures for patients with postmenopausal osteoporosis using gut microbiota analyses and feature selection approaches

Abstract: Osteoporosis (OP) is a metabolic bone disorder characterized by low bone mass and deterioration of micro-architectural bone tissue. The most common type of OP is postmenopausal osteoporosis (PMOP), with fragility fractures becoming a global burden for women. Recently, the gut microbiota has been connected to bone metabolism. The aim of this study was to characterize the gut microbiota signatures in PMOP patients and controls. Fecal samples from 21 PMOP patients and 37 controls were collected and analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Our findings show that the results of the association between BMD and gut microbiota differ in different skeletal sites. A previous study found that gut microbiota composition had a higher correlation with BMD values/T scores in the hip than in the lumbar spine (Huang et al, 2023). Only pelvic BMD was eventually found to have modest associations with gut microbiota in another Polygenic Risk Score (PRS) analysis, which was performed using 31 different sites of BMD as the outcome (Cheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the results of the association between BMD and gut microbiota differ in different skeletal sites. A previous study found that gut microbiota composition had a higher correlation with BMD values/T scores in the hip than in the lumbar spine (Huang et al, 2023). Only pelvic BMD was eventually found to have modest associations with gut microbiota in another Polygenic Risk Score (PRS) analysis, which was performed using 31 different sites of BMD as the outcome (Cheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%